Femtosecond laser-heating effect on the magnetization dynamics in perpendicularly magnetized Ta/CoFeB/MgO film - Bo Liu; Long Yang; Xuezhong Ruan; Jian-Wang Cai; Liang He; Hao Meng; Jing Wu; Yongbing Xu (New Journal of Physics, 2019)
We have studied the effect of ultrafast laser-heating on the magnetization dynamics of perpendicularly magnetized CoFeB film by means of the time-resolved magneto-optical Kerr rotation effect. The effective perpendicular magnetic anisotropy field ${H}_{K}$ is significantly decreased with enhancing the pump laser-fluence in a moderate range of 5–12 mJ cm ^−2 . The Gilbert damping, however, is found to be independent of the pump fluence. These findings provide a new method of separately manipulating the Gilbert damping and perpendicular magnetic anisotropy.